2021
DOI: 10.1007/s10815-021-02328-5
|View full text |Cite
|
Sign up to set email alerts
|

Autologous platelet-rich plasma treatment for moderate-severe Asherman syndrome: the first experience

Abstract: Purpose Treatment of Asherman syndrome (AS) presents a significant clinical challenge. Based on our in vitro data showing that PRP could activate endometrial cell proliferation and migration, we hypothesized that intrauterine infusion of autologous platelet-rich plasma (PRP) may improve endometrial regeneration and fertility outcomes in patients with moderate-severe AS. Materials and methods Subjects with moderate-severe AS were randomized to PRP or saline control administered following hysteroscopic adhesioly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
7
0
3
Order By: Relevance
“…Repeat hysteroscopy 8-10 weeks post-therapy failed to demonstrate any improvement in the reoccurrence of intrauterine adhesions and menstrual bleeding pattern compared to the control group [28]. In a similar trial of 15 patients with moderate to severe AS, 0.5-1 mL of PRP was infused immediately post-adhesiolysis, but no statistically significant difference was observed in the endometrial thickness or in the clinical and biochemical pregnancy rate [29]. In contrast, subendometrial injection of 5 mL of PRP in addition to coating the intrauterine lining with 5 mL of PRP gel immediately post-hysteroscopic adhesiolysis in 30 women with Asherman's syndrome was shown to result in a reduced rate of adhesions reforming and resulted in a significant increase in the duration of menses [30].…”
Section: Asherman's Syndromementioning
confidence: 91%
“…Repeat hysteroscopy 8-10 weeks post-therapy failed to demonstrate any improvement in the reoccurrence of intrauterine adhesions and menstrual bleeding pattern compared to the control group [28]. In a similar trial of 15 patients with moderate to severe AS, 0.5-1 mL of PRP was infused immediately post-adhesiolysis, but no statistically significant difference was observed in the endometrial thickness or in the clinical and biochemical pregnancy rate [29]. In contrast, subendometrial injection of 5 mL of PRP in addition to coating the intrauterine lining with 5 mL of PRP gel immediately post-hysteroscopic adhesiolysis in 30 women with Asherman's syndrome was shown to result in a reduced rate of adhesions reforming and resulted in a significant increase in the duration of menses [30].…”
Section: Asherman's Syndromementioning
confidence: 91%
“…of live births. 36 Although PRP did not considerably improve postsurgical adhesion, endometrial thickness, and the pregnancy rate after hysteroscopic adhesiolysis in some randomized clinical trials with a small sample size, 37,38 some successful pregnancy cases have been reported. 39 In our study, PRP demonstrated great potential for repairing a damaged intrauterine environment; thus, there is a need to reexamine the treatment protocol and conduct further clinical trials.…”
Section: Go Termmentioning
confidence: 95%
“…Platelet-rich plasma has also been studied for regeneration of the endometrium in animal models. [95][96][97] Finally, platelet-derived exosomes may play a regenerating role in the endometrium. A recent report suggests cell proliferation and wound healing in in vitro human endometrial cell lines when exposed to platelet-derived exsosomes.…”
Section: Endometrial Regeneration and Use Of Innovative Therapeuticsmentioning
confidence: 99%